Role of Organizational Trust as Mediation on the Effect of Knowledge Management on Innovative Behavior - Ekhsan, Muhamad; Badrianto, Yuan (PT. Riset Press International, 2024)
This study aims to analyze the direct effect of knowledge management on innovative behavior and examine the mediating role of organizational trust in the relationship. The sample used was 94 employees of manufacturing companies in the Bekasi area. Data collection using a 5-point Likert scale questionnaire. The data were analyzed using Partial Least Square (PLS) to test the research model and its hypotheses. The results prove that knowledge management has a significant positive effect on increasing innovative behavior. In addition, knowledge management is also proven to increase organizational trust. On the other hand, organizational trust has a significant positive effect on increasing employee innovative behavior. The results of path analysis also prove that organizational trust significantly mediates the effect of knowledge management on increasing innovative behavior. Thus this study succeeded in proving the proposed research model along with the four hypotheses. The practical implication is that companies need to pay balanced attention to the implementation of knowledge management programs and the cultivation of organizational trust in order to create an environment conducive to the growth of employee innovative behavior.